Keunggulan Power Mosfet dan IGBT sebagai Piranti Elektronika di Bidang Elektronika Daya - Sarita Yuniarti Hanum; Wiwien Hadikurniawati (Jurnal Ilmiah Dinamika Teknik, 2008)
Switching device is truly dominated by transistor, also by SCR that is hard to be off and relatively work slowly. This condition push the designers in every laboratories making of semi conductor device as in Motorola, IR, APT, IXYS, Siemens, Samsung and others that compete for finding switching device that have better capabilities. As the result, in marketing, now appear power switching device MOSFET and IGBT that compete each other